Analysis of the Impact Pandemic on KURDA Financing to UMKM Development in Sidoarjo Regency: Analisis Dampak Pandemi Pada Pembiayaan KURDA Terhadap Pengembangan UMKM di Kabupaten Sidoarjo - Hidayah, Nur; Megasari, Aisyah Darti; Siswanto; Siswohadi; Adinugroho, Mukhtar (Procedia of Social Sciences and Humanities, 2022)
This research aimed to analyze the role of KURDA Financing ( Regional People's Business Credit ), institutional characteristics of the business and the characteristics of entrepreneurs to the development of Micro, Small, and Medium Enterprises in the Sidoarjo Regency. The study design used descriptive approach qualitative and quantitative descriptive. Data were analyzed using analysis Crosstabulation and Chi-Square, a descriptive analysis technique.Crosstabulation based analysis and Chi-Square test, there is a significant relationship between the amount of financing, education, length of business, business development training, and the legality of the increase in revenue SMEs. While there was no significant relationship between the type of business and the ownership of the financial statements with a revenue increase of SMEs. SME revenue improvement opportunities are greatest in terms of the amount of financing. Of the 85% who obtain financing on Rp.5.000.000, 61% of SMEs could increase his income. The second biggest opportunities is occupied by SMEs that have financial statements, as many as 58% of the 82 respondents who had had financial reports may increase their income